Waste Analysis In Delivery Process Using The Lean Distribution Method - Adhella Ika Putri; Ernawati, Dira (The Indonesian Journal of Computer Science, 2024)
In the current era of globalization, the existence of goods delivery service companies supports almost every area of human life. In the process of delivering goods, PT. X always strives to provide fast and precise service. However, the problem faced by the company is the long lead time for delivery of goods. This study employs a lean distribution approach, applying Value Stream Mapping and identifying waste using the 8 waste framework. The research findings revealed waiting recapitulation of 20%, excess processing of 18%, overproduction of 17%, defects of 13%, non-utilized talent of 10%, inventory of 9%, transportation of 7%, and motion of 6%. With proposed improvements, the delivery process time can be reduced from 8243 minutes to 5929 minutes.